Explicit formula for the valuation of catastrophe put option with exponential jump and default risk. (August 2017) - Koo, Eunho; Kim, Geonwoo
Highlights: We propose an explicit pricing formula for catastrophe put option with default risk. The intensity based model is considered to describe the default risk. The multidimensional Girsanov theorem is used to derive the pricing formula. Numerical examples are provided to show the effects of default risk. Abstract: This paper concerns a catastrophe put option with default risk. Catastrophe events are described by the exponential jump model, and the default event of the option issuer is specified by the intensity based model with a stochastic intensity. Under this model, we derive the explicit analytical pricing formula of a catastrophe put option with default risk by using the multidimensional Girsanov theorem repeatedly. We also observe the effects of default risk on the prices of a catastrophe put option through the numerical experiment.